2010
DOI: 10.1152/ajprenal.00507.2009
|View full text |Cite
|
Sign up to set email alerts
|

Serum and urinary markers of early impairment of GFR in chronic kidney disease patients: diagnostic accuracy of urinary β-trace protein

Abstract: Donadio C. Serum and urinary markers of early impairment of GFR in chronic kidney disease patients: diagnostic accuracy of urinary ␤-trace protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 66 publications
1
43
0
1
Order By: Relevance
“…Urinary excretion of BTP has, thus, been used as a marker of renal dysfunction in animal models (39) and human studies (37,38,40,41). In a rat model experiment, a genetic model of spontaneous noninsulin-dependent diabetes mellitus accompanied by kidney dysfunction was used (39).…”
Section: Btp As a Urinary Biomarker Of Renal Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary excretion of BTP has, thus, been used as a marker of renal dysfunction in animal models (39) and human studies (37,38,40,41). In a rat model experiment, a genetic model of spontaneous noninsulin-dependent diabetes mellitus accompanied by kidney dysfunction was used (39).…”
Section: Btp As a Urinary Biomarker Of Renal Dysfunctionmentioning
confidence: 99%
“…Subsequently, two different studies with patients suffering from CKD showed that BTP was a useful marker for the early detection of renal tubular damage and that a BTP urine-based test can predict a slight GFR impairment in CKD patients (40,41).…”
Section: Btp As a Urinary Biomarker Of Renal Dysfunctionmentioning
confidence: 99%
“…BTP, also known as prostaglandin D2 synthase (PGDS), is a glycoprotein with a molecular mass of 23-29 kDa. With decreasing renal function, BTP plasma levels rise [13, 14] and virtually all BTP appears to be freely filtered through the glomerulus – whether this is followed by tubular reabsorption and degradation or not requires further study [12, 15]. Different BTP-based equations were proposed to translate plasma BTP levels to estimated GFR in different non-dialysis populations [16-18] and, more recently, in dialysis patients (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, b2M is known to correlate with GFR impairment in renal dysfunction [19]. The increase of b2M in CHF patients, in addition to its association with the severity of heart disease and renal impairment, suggests a new role for b2M as biomarker of heart failure progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%